Physiological assessment of a 16 day, 4385 km ultra-endurance mountain bike race: A case study - Hyldahl, R. D.; Gifford, J. R.; Davidson, L. E.; Hancock, C. R.; Hafen, P. S.; Parcell, A. C.; Mack, G. W. (Experimental Physiology, 2024)
The Tour Divide (TD) is a 4385 km ultra-endurance bicycle race that follows the continental divide from Canada to Mexico. In this case study, we performed a comprehensive molecular and physiological profile before and after the completion of the TD. Assessments were performed 35 days before the start (Pre-TD) and ~36 h after the finish (Post-TD). Total energy expenditure was assessed during the first 9 days by doubly labelled water (2H218O), abdominal and leg tissue volumes via MRI, and graded exercise tests to quantify fitness and substrate preference. Vastus lateralis muscle biopsies were taken to measure mitochondrial function via respirometry, and vascular function was assessed using Doppler ultrasound. The 47-year-old male subject took 16 days 7 h 45 min to complete the route. He rode an average of 16.8 h/day. Neither maximal O2 uptake nor maximal power output changed pre- to post-TD. Measurement of total energy expenditure and dietary recall records suggested maintenance of energy balance, which was supported by the lack of change in body weight. The subject lost both appendicular and trunk fat mass and gained leg lean mass pre- to post-TD. Skeletal muscle mitochondrial and vascular endothelial function decreased pre- to post-TD. Overall, exercise performance was maintained despite reductions in muscle mitochondrial and vascular endothelial function post-TD, suggesting a metabolic reserve in our highly trained athlete.